Fluid mechanics in circulating tumour cells: Role in metastasis and treatment strategies - Shivam Rajput; Pramod Kumar Sharma; Rishabha Malviya (Elsevier, 2023)
Cancer patients have a shorter life expectancy because of metastasis, which is the dynamic chain of events that leads to the spread of tumour cells to distant places inside the body. Cancer's development, spread, metastasis, and treatment all involve fluid mechanics in some way. Cancer cells and their associated components take advantage of the body's many fluid systems as a means of dissemination throughout the body and colonisation of distant organs. Cancerous tissues rely on the blood supply for oxygen and nutrition, metastasis to other organs, and medication delivery. Cancer cells' ability to travel from the main tumour, extravasate, and seed metastases can be enhanced by exploiting the flow mechanics of the blood and lymphatic circulatory systems. Cancer cell survival in the circulation and the regulation of organotropic seeding patterns are affected by flow rates, channel size, and shear stress. Therefore, cancer cells not only use these fluids as a mode of transport throughout the body, but also as a fertile ground to seed distant metastases by taking advantage of the fundamental physical forces among these fluids. Metastasis, tumor growth, & nanoparticle-mediated medication delivery is all under the control of multiscale flow-structure interaction processes, whereas an increase in interstitial pressure is caused by the tumour vasculature's irregularity and leakiness. This Review discusses the role that fluids play in metastasis, including the forces and stresses that are utilised by circulating tumour cells & tumour-associated factors. Given the intriguing concerns raised by the role of physiological fluids and their mechanics in the biology of the metastatic cascade, gaining insight into this process may reveal a novel strategy for intercepting cancer cells on their route.